A Mixture of Baicalein, Wogonin, and Oroxylin-A Inhibits EMT in the A549 Cell Line via the PI3K/AKT-TWIST1-Glycolysis Pathway - Cao, Hui-Juan; Zhou, Wei; Xian, Xiao-Le; Sun, Shu-Jun; Ding, Pei-Jie; Tian, Chun-Yu; Tian, Fu-Ling; Jiang, Chun-Hua; Fu, Ting-Ting; Zhao, Shu; Dai, Jian-Ye (Frontiers in Pharmacology, 2022)
Non–small cell lung cancer (NSCLC) is a worldwide disease with high morbidity and mortality, which is most derived from its metastasis.Some researchers show that the epithelial–mesenchymal transition (EMT) process promotes lung cancer cells migration and invasion, leading to NSCLC metastasis. Total Flavonoid Aglycones Extract (TFAE) isolated from Scutellaria baicalensis was reported to inhibit tumor growth and induce apoptosis. In this study, we found that baicalein, wogonin, and oroxylin–A were the active compounds of TFAE. After reconstructing with these three compounds(baicalein(65.8%),wogonin(21.2%), and oroxylin–A(13.0%)),the recondtructed TFAE(reTFAE) present inhibitory effect on the EMT process of A549 cells. Then, bioinformatic technology was employed to elucidate the potential pharmacodynamic mechanism network of reTFAE. We identified the relationship between reTFAE and PI3K/Akt signaling pathways, with TWIST1 as the key protein. LY294002, the inhibitor of PI3K/Akt signaling pathway, and knock–down TWIST1 could significantly enhance the efficacy of reTFAE, and, with increasing expression of epithelial markers and decreasing expression of mesenchymal markers in A549 cells at the same time. Furthermore, stable isotop dimenthyl–labeled proteomic technology was conducted to complement the follow–up mechanism that the EMT–inhibition process may be realized through glycolysis pathway.In conclusion,we claim that TWIST1–targeted flavonoids could provide a new stratedy to inhibit EMT progress for the treatment of NSCLC.